SOSIALISASI IMPLEMENTASI KEBIJAKAN PELAYANAN PRIMA DALAM PENINGKATAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS DELI TUA - Selamat Ginting; Diana Sinulingga; Alprindo Sembiring; Akhmad Fatikhus (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Excellent service is a new strategy in an effort to increase patient satisfaction in puskesmas services. Along with the demands of the community for the quality of services at the Puskesmas, it is necessary to have good knowledge and understanding of everyone who works at the Puskesmas so that the implementation of excellent service policies in increasing outpatient satisfaction is carried out through socialization efforts. It is hoped that with the socialization there will be cohesiveness of all officers in outpatient services in implementing the policy.